2020
DOI: 10.1248/cpb.c19-00646
|View full text |Cite
|
Sign up to set email alerts
|

CTRP12 Ameliorated Lipopolysaccharide-Induced Cardiomyocyte Injury

Abstract: C1q/tumor necrosis factor (TNF)-related protein 12 (CTRP12) is a secretory protein that participates in the regulation of glucose and lipid metabolism in obesity and diabetes. Its role in cardiovascular disease, particularly sepsis-induced cardiac injury, is unclear. Here, we stimulated cardiomyocytes with lipopolysaccharide (LPS) to establish an in vitro cardiomyocyte injury model and CTRP12 was overexpressed with an adenovirus delivery system. Overexpression of CTRP12 reduced the transcription and release of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Adiponectin is known to protect against atherosclerosis in animal models 32,33 . Although CTRP12 was reported to participate in the occurrence and development of cardiovascular disease [22][23][24] , its role in atherogenesis is still largely unknown. Our in vivo experiments demonstrated that aortic plaque burden was significantly lower in apoE −/− mice overexpressing CTRP12 than that in apoE −/− littermates.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Adiponectin is known to protect against atherosclerosis in animal models 32,33 . Although CTRP12 was reported to participate in the occurrence and development of cardiovascular disease [22][23][24] , its role in atherogenesis is still largely unknown. Our in vivo experiments demonstrated that aortic plaque burden was significantly lower in apoE −/− mice overexpressing CTRP12 than that in apoE −/− littermates.…”
Section: Discussionmentioning
confidence: 99%
“…of pro-inflammatory cytokines 58 . Treatment with recombinant CTRP12 decreases the expression of MCP-1, TNFα and IL-6 in LPS-treated macrophages 59 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial gain‐of‐function studies in mice have revealed antidiabetic [12] and anti‐inflammatory [27] activities of CTRP12. Recent studies also implicated a protective role of CTRP12 in the cardiovascular system [40,41]. In the context of metabolism, CTRP12 acts through insulin‐dependent and insulin‐independent pathways to control glucose metabolism in liver and adipose tissue [12].…”
mentioning
confidence: 99%